Qur’anic Gender Equality and Arab Patriarchy: Implications for Islamic Education - Muhamad Arfan; Junaidi Junaidi (Newinera Publisher, 2025)
This article examines gender interpretation from the perspectives of the Qur’an and Arab tradition and explores its implications for the development of Islamic education grounded in equality and universal Islamic values. The study employs a qualitative literature review using content analysis, historical analysis, and hermeneutic approaches to classical and contemporary scholarship on gender, Qur’anic exegesis, Arab tradition, and Islamic education. The findings reveal that the Qur’an positions men and women as equal moral agents through the principles of ontological equality, the shared mandate of vicegerency (khilāfah), recognition of women’s leadership, and equal rights to social, political, and economic participation. In contrast, many forms of women’s subordination are rooted in patriarchal social structures and Arab cultural traditions that subsequently influenced certain interpretations of Islamic law and exegesis. These findings underscore the importance of Islamic education as a space for critical literacy that distinguishes between the universal teachings of Islam and historically contingent patriarchal traditions. Islamic education informed by al-musāwah (equality), al-‘adālah (justice), al-ḥurriyyah (freedom), and al-tasāmuḥ (tolerance) has the potential to serve as a strategic instrument for fostering inclusive religious consciousness and addressing the challenges of contemporary global society.